-29-j=0

Simple and best practice solution for -29-j=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -29-j=0 equation:


Simplifying
-29 + -1j = 0

Solving
-29 + -1j = 0

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '29' to each side of the equation.
-29 + 29 + -1j = 0 + 29

Combine like terms: -29 + 29 = 0
0 + -1j = 0 + 29
-1j = 0 + 29

Combine like terms: 0 + 29 = 29
-1j = 29

Divide each side by '-1'.
j = -29

Simplifying
j = -29

See similar equations:

| 7a-3=-2a | | x^2-1x+7=49 | | 39.2=-4.9x^2+29.4x+0 | | 4x+18=2x+12 | | 3(x+2y)=2x+5y | | 3(x+2y)=2x+y | | -5x+20=1+x | | -2500+-200x=12 | | 10b=16 | | m^2+m+42=0 | | 5(5h+15)-6h=18 | | 4x-2+3x=26 | | 9g-5g= | | -2500+-200x=-12000 | | 3x-2x+10=82 | | chi*cken= | | -2500+-200x=-5100 | | 5x+10-3=5(x+2)3 | | 6x-8y=9 | | -16t^2+144t-320=0 | | 39(g-7)=2(10+g) | | -10x=-11 | | 6h+3(-h-3)=-9 | | (y-7)-(y+3)=6y | | -4(v-6)=-2+18 | | 6y-10=20+y | | 3-2x-5=16 | | 3k+15=-2(3k-6) | | -33=-6x+x+2 | | 25x-37=113 | | 7.3y-5.18= | | 2y-5x=607 |

Equations solver categories